Liberace with his mother at the London Waldorf Astoria (Module II, 2013)
England. London. Pianist and entertainer Liberace meets fans at the Waldorf Astoria hotel, with his mother. Liberace meets a Pearly King and Queen. Liberace addresses the crowd of fans and thanks them for their wonderful work. Liberace exits through crowds of fans.